CORRELATION AND PATH ANALYSIS FOR YIELD AND ITS YSIS FOR YIELD AND ITS RELATED TRAITS IN F TED TRAITS IN F3 GENERATION OF BLACKGRAM [ CKGRAM [Vigna mungo (L.) Hepper] (L.) Hepper] - SHILPA CHAUHAN , RANJANA PATIAL, R. K. MITTAL; V. K. SOOD (The Bioscan, 2018)
The present investigation on correlation and path coefficient analysis for yield and yield contributing characters in F3 population of 21 families developed by crossing 12 parents with three testers, ascertain the genetic and phenotypic correlation and contribution of these traits towards the yield directly and indirectly in blackgram. The results showed that seed yield per plant exhibited significant and positive correlation with biological yield per plant (r=0.730), harvest index (r=0.522), seeds per pod (r=0.466), pods per plant (r=0.428) and pod length (r=0.332). Path coefficient analysis depicted that biological yield per plant (0.719) and harvest index (0.485) had a direct influence on seed yield in positive direction. This predicted that while designing a breeding strategy for the improvement of blackgram these traits should be kept in mind to enhance seed yield of urdbean in the future breeding programs.